The posthumanist challenge to teaching or teaching's challenge to posthumanism: a neohumanist proposal of nearness in education. Issue 5 (3rd September 2022) - Kouppanou, Anna
ABSTRACT: Pedagogical approaches emanating from posthumanist and neomaterialist theoretical frameworks can potentially redefine what learning and teaching are. In this paper, I argue, however, that these discussions are marked by a distinct absence, having to do with the role of teachers and the nature of teaching itself. Attempting to make up for this lack, I discuss here posthumanism's and neomaterialism's critique of humanism – indeed, in connection to certain reconfigurations of agency as relationality existing between human and non-human species and of learning as encounter between species. I then deliberate on an alternative kind of agency that reconfigures existence, as posthumanism and neomaterialsm do, but also salvages some useful aspects of human agency, which are necessary for discussing teaching and learning. In this way, I am finally able to describe a type of neohumanism illuminated by the state of being a child (childness) and by a certain reconceptualization of teaching and learning.